EFEKTIVITAS ZONA SELAMAT SEKOLAH DAN KINERJA RUAS JALAN (STUDI KASUS: ZOSS SD NEGERI 4 DALUNG) - N. Nurhakim; Dewa Ayu Nyoman Sriastuti; I Made Ardantha (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2018)
ABSTRACT School safety zone (ZoSS) is a government program that began in 2006. The program aims to reduce the number of traffic accidents, especially school children. The use of ZoSS is still not optimal because there are still many road users passing ZoSS at high speed, school children have not used ZoSS facilities, as well as the surrounding community including teachers and parents who do not understand the existence of ZoSS. The approach taken is by observing the behavior of pedestrians, especially school children, the introductory behavior of school children, the behavior of drivers, the speed of vehicles passing on ZoSS, the volume of vehicles that are then analyzed and the performance of the road. The results of the study showed that the behavior of the crossers was 60.01% that meaning ZoSS was effective. The level of introductory behavior is 67.65% that meaning ZoSS was effective. The percentage of vehicles that follow ZoSS regulations is 32.58% that meaning ZoSS was less effective. The performance of the road segment in the ZoSS segment has a degree of saturation of 0.09 service level A. Keywords: driver, vehicle, ZoSS